Efficacy and safety of trastuzumab deruxtecan in gastrointestinal malignancies: a systemic review and meta-analysis - Hussain, Ali; Iqbal, Qamar; Isaac, Sangeetha; Shariff, Faisal; Tariq, Ezza; Awais, Hassan; Mainkar, Nayan; Reis, Heidi Lynn; Arora, Aakriti; Deotare, Akshay; Tasleem, Azka; Valasapalli, Srijan; et al. (Frontiers in Gastroenterology, 2025)
BackgroundTrastuzumab deruxtecan (T-DXd) is an antibody-drug conjugate (ADC) that is effective in treating gastrointestinal (GI) cancers. However, the significant variability in its reported efficacy and safety profiles is likely due to differences in trial designs, patient populations, and clinical settings. This systematic review and meta-analysis aimed to consolidate current evidence on the efficacy and safety of T-DXd in human epidermal growth factor receptor 2 (HER2)-positive GI malignancies.MethodsWe conducted a systematic review and meta-analysis following the Preferred Reporting Items for Systemic Reviews and Meta-Analysis guidelines (PRISMA), utilizing the Medline, Embase, Cochrane Central, and ClinicalTrials.gov databases. Out of 5,594 articles reviewed, 10 studies were ultimately included after both primary and secondary screenings, providing data on the outcomes and safety of T-DXd in HER2-positive GI malignancies. The National Institute of Health quality assessment tool was employed to evaluate the quality of the studies. Pooled analyses were performed using the ‘meta’ package (Schwarzer et al., R programming language), and proportions with 95% confidence intervals (CIs) were calculated.ResultsWe identified 653 patients treated with T-DXd for HER2-positive GI malignancies in 10 studies. The median age of the patients was 64.5 years (27–85) and 53% were male. The median follow-up duration was 5.9 months (0.5–30.5). The median overall survival and progression-free survival were 11.15 (1.4–20.8) and 5.6 months (2.6–8.7), respectively. The pooled objective response rate (ORR) was 36.9% (95% CI:31.5%–42.5%, I² = 41%, n = 589), with partial response and complete response rates of 35.2% (95% CI:31.1%–39.5%, I² = 0%, n = 516) and 1.3% (95% CI: 0.0%–4.7%, I² = 73%, n = 516), respectively. The median duration of response (DoR) was 7 months (0.7–22.3). Reported adverse events included anemia, febrile neutropenia, thrombocytopenia, diarrhea, nausea, interstitial lung disease/pneumonitis, heart failure, and hepatitis. For the 5.4 mg/kg dose, grade 3/4 adverse events were reported in 67 patients. For the 6.4 mg/kg dose, 146 grade 3/4 adverse events were reported.ConclusionsThis meta-analysis supports the efficacy of T-DXd in patients with HER2-positive GI malignancies with a moderate ORR, even in patients who have experienced disease progression after multiple lines of therapy. Overall, T-DXd is well-tolerated, with limited severe adverse events. These findings validate existing research and underscore the need for further clinical trials, particularly in earlier lines of treatment.